Design of IMC based PI Controller for Paper Machine Headbox - Saini, Parvesh (Journal of Graphic Era University, 2023)
<span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*277.49px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.938603);" role="presentation">Headbox is one the major process of a <span dir="ltr" style="left: calc(var(--scale-factor)*236.09px); top: calc(var(--scale-factor)*277.49px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.872868);" role="presentation">paper <span dir="ltr" style="left: calc(var(--scale-factor)*262.01px); top: calc(var(--scale-factor)*277.49px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.949389);" role="presentation">machine which is vulnerable to many disturbances. Its efficient <span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*289.01px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.950188);" role="presentation">control is highly required because any disturbance in the process greatly affects the working of <span dir="ltr" style="left: calc(var(--scale-factor)*471.22px); top: calc(var(--scale-factor)*289.01px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.873747);" role="presentation">the <span dir="ltr" style="left: calc(var(--scale-factor)*487.18px); top: calc(var(--scale-factor)*289.01px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.886028);" role="presentation">headbox. <span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*300.53px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.913998);" role="presentation">Various tuning techniques have been designed and applied on paper machine headbox. <span dir="ltr" style="left: calc(var(--scale-factor)*429.22px); top: calc(var(--scale-factor)*300.53px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.896445);" role="presentation">This paper presents <span dir="ltr" style="left: calc(var(--scale-factor)*511.30px); top: calc(var(--scale-factor)*300.53px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.873747);" role="presentation">the <span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*311.93px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.888425);" role="presentation">design <span dir="ltr" style="left: calc(var(--scale-factor)*100.58px); top: calc(var(--scale-factor)*311.93px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.92755);" role="presentation">and analysis of Internal Model Control (IMC) based <span dir="ltr" style="left: calc(var(--scale-factor)*311.83px); top: calc(var(--scale-factor)*311.93px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.9947);" role="presentation">Multi Input – <span dir="ltr" style="left: calc(var(--scale-factor)*367.63px); top: calc(var(--scale-factor)*311.93px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.973682);" role="presentation">Multi Output (<span dir="ltr" style="left: calc(var(--scale-factor)*426.10px); top: calc(var(--scale-factor)*311.93px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(1.04264);" role="presentation">MIMO) - <span dir="ltr" style="left: calc(var(--scale-factor)*466.06px); top: calc(var(--scale-factor)*311.93px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.930169);" role="presentation">Proportional – <span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*323.45px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.946594);" role="presentation">Integral (PI) controller for paper machine headbox. Along with transient response, <span dir="ltr" style="left: calc(var(--scale-factor)*415.90px); top: calc(var(--scale-factor)*323.45px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.949621);" role="presentation">integral error <span dir="ltr" style="left: calc(var(--scale-factor)*473.14px); top: calc(var(--scale-factor)*323.45px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.899481);" role="presentation">performance <span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*334.97px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.909573);" role="presentation">indices <span dir="ltr" style="left: calc(var(--scale-factor)*102.86px); top: calc(var(--scale-factor)*334.97px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.965233);" role="presentation">(ISE, IAE, ITSE, <span dir="ltr" style="left: calc(var(--scale-factor)*174.38px); top: calc(var(--scale-factor)*334.97px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.86296);" role="presentation">and <span dir="ltr" style="left: calc(var(--scale-factor)*191.33px); top: calc(var(--scale-factor)*334.97px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(1.05122);" role="presentation">ITAE) <span dir="ltr" style="left: calc(var(--scale-factor)*220.01px); top: calc(var(--scale-factor)*334.97px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.865967);" role="presentation">have <span dir="ltr" style="left: calc(var(--scale-factor)*241.37px); top: calc(var(--scale-factor)*334.97px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.884786);" role="presentation">also been obtained. <span dir="ltr" style="left: calc(var(--scale-factor)*320.95px); top: calc(var(--scale-factor)*334.97px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.902094);" role="presentation">The performance of designed <span dir="ltr" style="left: calc(var(--scale-factor)*441.34px); top: calc(var(--scale-factor)*334.97px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.950039);" role="presentation">multivariable <span dir="ltr" style="left: calc(var(--scale-factor)*497.14px); top: calc(var(--scale-factor)*334.97px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(1.032);" role="presentation">IMC – <span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*346.49px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.915635);" role="presentation">PI Controller has been compared with the conventional ZN - <span dir="ltr" style="left: calc(var(--scale-factor)*316.99px); top: calc(var(--scale-factor)*346.49px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.953728);" role="presentation">PI controller.